Large gastroduodenal artery pseudoaneurysm, arterioportal fistula and portal vein stenosis in chronic pancreatitis treated using combined transarterial embolization and transportal stenting: A case report. Issue 52 (30th December 2022) - Lim, Sung Gong; Park, Sung Eun; Nam, In Chul; Choi, Ho Cheol; Won, Jung Ho; Jo, Sa Hong; Baek, Hye Jin; Moon, Jin Il; Cho, Eun; Jang, Jae Yool
Abstract : Rationale: Chronic pancreatitis is an ongoing fibroinflammatory disease of the pancreas characterized by irreversible damage to the pancreatic parenchyma and ductal system. Besides, chronic pancreatitis can present with a variety of life-threatening complications. Patient concerns: The patients visited our hospital due to abdominal pain and anemia, and had chronic pancreatitis as an underlying disease. Diagnoses: Computed tomography showed a large gastroduodenal artery pseudoaneurysm, arterioportal vein fistula, and portal vein stenosis. Interventions: We would like to report the successful use of the coils, and N-butyl cyanoacrylate glue for the therapeutic embolization of the pseudoaneurysm and fistula between the gastroduodenal artery and the portal vein, and stenting for portal vein stenosis. Outcomes: On the day following the endovascular management, the patient reported remission of abdominal pain, and hemoglobin level returned to normal after transfusion. It was confirmed that it was still well maintained in the follow-up examination after 1 month. Lessons: Although chronic pancreatitis causes many vascular complications, simultaneous occurrence of these lesions is extremely rare. Herein, we share our experience with a unique case of an extrahepatic arterioportal fistula induced by the rupture of gastroduodenal artery pseudoaneurysm with concomitant portal vein stenosis. In these complex cases, combined transarterial embolization and transportal stenting can be helpful.